Crystal structure of methyl (6-(2-fluorobenzoyl)-5-chloro- 2-benzoxazolinon-3-yl)-acetate, C17H11CIFNO5 - Aydin A.; Diindar Y.; Akkurt M.; Büyükgüngör, Orhan; Sahin M.F. (Walter de Gruyter GmbH, 2006)
C17H11CIFNO5, monoclinic, P12(1)/cl (no. 14), a = 7.489(5) angstrom, b = 18.367(5) angstrom, c = 11.752(5) angstrom, beta = 94.222(5)degrees. V = 1612.1 angstrom(3), Z = 4, R-gt(F) = 0.032, wR(ref)(F-2) = 0.083, T = 293 K.
Keywords: Crystallography; QD901-999; Physics; QC1-999